The Influence of Financial Management on Financial Literacy of MSMEs - Jesus, Herminio da Cruz (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the effect of financial management on the financial literacy of Micro, Small, and Medium Enterprise (MSME) actors in Timor Leste. MSMEs play a vital role in economic development; however, limited financial literacy and weak financial management practices continue to hinder business sustainability. This research employed a quantitative approach using a survey method, with data collected through structured questionnaires distributed to MSME actors selected through purposive sampling. Financial management was measured using indicators of financial planning, transaction recording, budgeting, cash flow management, and financial evaluation, while financial literacy was assessed based on financial knowledge, attitudes, and financial behavior. The collected data were analyzed using descriptive statistics and simple linear regression techniques. The results indicate that the level of financial management among MSME actors is moderate, with stronger performance in basic recording and cash flow management than in long-term financial planning and evaluation. Financial literacy was also found to be at a moderate level, particularly in terms of basic financial knowledge. Furthermore, regression analysis reveals that financial management has a positive and significant effect on financial literacy, suggesting that better financial management practices contribute to improved financial understanding and behavior. These findings highlight the importance of integrating financial management training with financial literacy programs to enhance MSME competitiveness and sustainability. The study contributes theoretically to the literature by emphasizing experiential learning in financial management and provides practical implications for policymakers and development institutions in designing effective MSME empowerment strategies in Timor Leste